2017
DOI: 10.18510/ijthr.2017.413
|View full text |Cite
|
Sign up to set email alerts
|

Need for Professionalism and Quality Service of the Tourist Guides in Oman

Abstract: PURPOSEThe objectives of the study are to investigate the factors impeding the professionalism of the tourist guides in Oman and to analyze the service quality improvement of the tourist guides.DESIGN/METHODOLOGY/APPROACH56 samples were collected from the tourist guides in Oman working in public and private sector, and the samples were selected on a random sampling basis. Using a well-defined questionnaire data was collected, analyzed and interpreted to derive the conclusion.FINDINGSThe empirical results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…A major constraint for a tourism establishment in Oman is project funding, and managing the tourism business (Al Harthi, 2017). The Government should provide financial and strategic support to the tourism entrepreneurs to support the tourism industry which can generate new jobs and could uplift economic development (Alani et al, 2017). Omani youth who have innovative ideas need financial support as a successful tourism entrepreneur would be able to provide employment opportunities to many more (Sokhalingam, Manimekalai, & Sudhahar, 2013).…”
Section: Financial Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…A major constraint for a tourism establishment in Oman is project funding, and managing the tourism business (Al Harthi, 2017). The Government should provide financial and strategic support to the tourism entrepreneurs to support the tourism industry which can generate new jobs and could uplift economic development (Alani et al, 2017). Omani youth who have innovative ideas need financial support as a successful tourism entrepreneur would be able to provide employment opportunities to many more (Sokhalingam, Manimekalai, & Sudhahar, 2013).…”
Section: Financial Constraintsmentioning
confidence: 99%
“…Nondiscrimination of gender, physical working conditions and promotional opportunities encourage people to venture into the tourism sector whereas high risks of accidents in Oman, non-tourism spouse preferences, and traditional values of Oman discouraged them (Khan & Krishnamurthy, 2016). The tourist guide profession is not considered as a prestigious profession in the society of Oman but (Alani et al, 2017) and suggested for implementing specialized courses by the government in relates to tourism. The tourism sector in Oman is suffering due to factors such as strict policies, financial performance, and lack of support from the government of Oman (Stanković & Đukić, 2009).…”
Section: Challenges Faced By Omani Tourism Entrepreneursmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation is one of the successful indirect management tools that help managers to activate the principles of sustainable tourism at the archaeological sites (McDonnell, 2001;Poudel & Nyaupane, 2013). In this regard, Interpretation can be divided into two groups: guided and non-guided interpretation (Ababneh, 2017;Alani et al, 2017;Alazaizeh et al, 2019). Guided interpretation is providing the information to the visitors through face-to-face interaction and direct personal communication with a tour guide (McDonnell, 2001;Reisinger & Steiner, 2006), while nonguided interpretation is depending on transfer the information by publications and signs without intervention the tour guide (Rabotic, 2008;Poudel & Nyaupane, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Professionalism in tour guiding is essential and has brought attention to many researchers (Alani & Khan, 2017;Ap & Wong, 2001;Lai, 2014;Mak et al, 2011;Prakash & Chowdhary, 2010;. Lai (2014) argued that professionalism affects service quality and tourist satisfaction.…”
Section: Professionalism In Tour Guidingmentioning
confidence: 99%